New Trend of Digital Diplomacy in Pakistan: Amelioration or Deterioration - Farzana Zaheer Syed; Asia Saif Alvi, (ASIAN Journal of International Peace & Security (AJIPS), 2021)
The study intended to focus on diplomacy as an essential component of the foreign policy established by the states for the magnification of international affairs. Advanced technologies have had a massive impact on foreign policy and have reworked the traditional diplomatic itinerary. The results were found using a qualitative research approach and an exploratory method. The research looked into how Pakistan uses the internet to modernize its effective foreign policy. How effective are new digital diplomatic strategies in Pakistan's foreign policy? The present study aimed to assess the model of digital diplomacy as part of Pakistan's foreign policy, which has focused primarily on the use of social media in the arena of diplomatic courses. It examines the benefits and drawbacks of digital diplomatic services and argues that states cannot justify digital diplomatic practices. The New Democratic government in Pakistan has a firm stance on digitizing the country's diplomatic trends. Digital diplomacy and Internet services (ICTs) have the potential to strengthen the state's foreign policy standing in the minds of regional and international audiences. A careful implication of the new trends in foreign affairs can diminish the bullying and deterioration.